Quizizz-assisted case and team-based project: a pathway to enhance problem-solving and digital literacy - Situmorang, Prima Lestari; Arianti, Juli; Sinambela, Krisanty Mey (Indonesian Institute for Counseling, Education and Theraphy, 2025)
The study aims to improve students' problem- solving skills and digital literacy by implementing the case method assisted by Quizizz. This research was conducted on fifth-semester economic education students. This research is a qualitative Classroom Action Research (PTK). The research instruments used tests, observations, and interviews. The population in this study were 20 people. The sampling technique used Purposive- Sampling so that the research sample amounted to 30 people. The results of the study were that there was an increase in the Student Learning Completeness Score (KPM) at 3 meetings. Learning completeness has an average of 74% with an average increase of 14%. There are 4 aspects assessed in problem-solving skills. 100% have been able to find problems in the case, in aspect 2, 83.33% of students mastered the aspect of transforming information. 50% of students have been able to develop a problem-solving plan, and 26.67% of students are able to conclude a solution to the problem. Meanwhile, through the application of the Quizizz application, 60% of students who experienced an increase in digital literacy and the rest could not connect to the internet network.